Implementasi PSAP No. 2 dalam laporan realisasi anggaran di Badan Keuangan dan Aset Daerah Kota Manado - Panggabean, Elisabet; Tinangon , Jantje J.; Wokas , Heince R. N. (Yayasan Widyantara Nawasena Raharja, 2025)
Statement of Government Accounting Standards (PSAP) No. 2 in preparing and reporting the Budget Realization Report (LRA) at the Manado City Regional Finance and Assets Agency. The Budget Realization Report is an important component of government financial reports which presents information regarding income, expenditure, surplus/deficit, and funding compared to the budget. This standard requires that the Budget Realization Report be prepared on a cash basis, with income recognized when cash is received and expenses recognized when cash is disbursed. The aim of this research is to determine the implementation of PSAP No. 2 in the budget realization report at the Manado City Regional Finance and Assets Agency. The analytical method used to discuss the problems in this research uses a qualitative descriptive method with data collection techniques through interviews, documentation and observation. The research results show that the revenue and expenditure recognition process in the Budget Realization Report is in accordance with PSAP No. 2, where income is recognized when cash is received and expenditure when cash is disbursed. The report structure presents a comparison of budget with realization, including budget elements, realization and differences, thereby providing transparency regarding budget achievements. The budget surplus is managed to finance reserves, development investment and debt repayment, while the deficit is overcome through optimizing Original Regional Income (PAD) and budget revision. Implementation of PSAP No. 2 in the Budget Realization Report at the Manado City Regional Financial and Asset Agency is in accordance with applicable standards. The preparation of reports shows transparency and accountability that supports effective and efficient financial decision making.